Motivasi dan Hasil Belajar Siswa pada Pembelajaran IPA dengan Menggunakan Media Interaktif Pear Deck dan Quizizz Berbantuan Zoom - Royalia, Krisanti; Aeni, Ani Nur; Sujana, Atep (Jurnal Pena Ilmiah, 2021)
This research is to find out of motivation and learning outcomes of students in science by using interactive learning media Pear Deck and Quizizz assisted by Zoom. The purpose of this research is to find out how the implementation of learning by using interactive media Pear Deck and Quizizz, how the motivations, and how the results of student learning. The method used in this research is descriptive qualitative. The subjects in this research is 6th grader from SDN Gudangkopi II. The research instruments used were observation guidelines and test questions. This instrument is validated by expert opinion. The results of this research of implementation learning are 91.6% for the seriousness of the students, 83.3% for the discipline of the students, and 86.1% for the agility of the students. Meanwhile for students' motivation, 86.1% for effort, 94.4% for perseverance, and 88.8% for self-confidence. And for the student learning outcomes obtained an average score of 88.3.